A BEMA DOOR FROM THE GREAT METEORO MONASTERY ATTRIBUTED TO THE PAINTER THEOFANES THE CRETAN - Papadimitriou, Paraskevi (Analecta Stagorum et Meteororum, 2022)
In the sacristy of the Monastery of Great Meteoron, there is an unpublished altar door of the simple painted type. On its surface, at the upper part, the scene of the Annunciation is depicted, while in the lower and smaller section, the busts of the leading apostles Peter and Paul are shown. The iconographic, stylistic, and particularly the artistic characteristics of the altar door allow for its classification within the Cretan school, specifically within the artistic activity of the painter Theophanes the Cretan. The altar door is likely dated to the third decade of the 16th century.